Pulmonary perfusion imaging and delayed imaging to measure pulmonary capillary permeability in pulmonary contusion. Issue 6 (12th April 2022) - Xiong, Kai; Li, Shicong; Yu, Yao; Duan, Shuning; Zhang, Peng; Wang, Peng; Li, Xin; Chen, Yuan; Cui, Yuantao; Wang, Yuanguo; Shen, Yiming; Yang, Zhaoyu; et al.
Abstract : Purpose: Explore the application value of pulmonary perfusion imaging and delayed imaging for evaluating pulmonary capillary permeability. Materials and methods: After establishing a rat model of pulmonary contusion, changes in the metabolic index of technetium-99m macroaggregated albumin (99mTC-MAA) in the lungs of model rats were evaluated for two consecutive days. 99mTC-MAA metabolic indices of rat lungs with pulmonary contusion of varying severity (mild, moderate, and severe) were correlated with lung wet/dry weight ratio (W/D) and Evans blue extravasation. Finally, the method was validated in patients with pulmonary contusion and one healthy volunteer. Results: The 99mTC-MAA metabolic index was 23.56% ± 2.44% in healthy control (HC) rat lung, 8.56% ± 3.42% immediately after lung contusion (d0), 8.35% ± 3.20% after 1 day (d1), and 17.45% ± 6.44% after 2 days (d2); indices at d0 and d1 were significantly higher than those at HC ( P < 0.05). The metabolic index of 99mTC-MAA in lung had significant negative correlations with W/D ( r = −0.8025; P = 0.0092) and Evans blue extravasation ( r = −0.9356; P = 0.0002). Metabolic and oxygenation indices of 99mTC-MAA exhibited a significant positive linear correlation in patients with pulmonary contusion ( r = 0.8925; P = 0.0416). Conclusion: Pulmonary perfusion and delayed imaging of 99mTC-MAA have potential value for evaluating pulmonary capillary permeability.